2015
DOI: 10.1111/cmi.12544
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus-induced miR-142-5p elicits proviral milieu by targeting non-canonical transforming growth factor beta signalling and apoptosis in cells

Abstract: MicroRNA (miRNA) expression is significantly influenced by viral infection, because of either host antiviral defences or proviral factors resulting in the modulation of viral propagation. This study was undertaken to identify and analyse the significance of cellular miRNAs during rotavirus (SA11 or KU) infection. Sixteen differentially regulated miRNAs were identified during rotavirus infection of which hsa-miR-142-5p was up-regulated and validated by quantitative polymerase chain reaction. Exogenous expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 54 publications
4
35
0
1
Order By: Relevance
“…A latest research reported that up-regulated miR-142-5p inhibits TGF-β-induced apoptosis via targeting TGFBR2 and SMAD3 in rotavirus infection model [33]. Our studies indicated that miR-142-5p overexpression significantly downregulated SMAD3 to diminish TGF-β-induced growth arrest, supporting Chanda et al research from several tumor cell lines.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A latest research reported that up-regulated miR-142-5p inhibits TGF-β-induced apoptosis via targeting TGFBR2 and SMAD3 in rotavirus infection model [33]. Our studies indicated that miR-142-5p overexpression significantly downregulated SMAD3 to diminish TGF-β-induced growth arrest, supporting Chanda et al research from several tumor cell lines.…”
Section: Discussionsupporting
confidence: 87%
“…We analyzed the upstream sequence of the miR-142 gene and also found a MYC-binding site in its promoter, suggesting that MYC regulates the biosynthesis of miR-142 precursors. Collectively, our and other studies indicated that miR-142-5p/3p attenuate TGF-β signal transduction by targeting TGFBRI/II and SMAD3 [33, 41]. A combinatorial miRNA-TF feedback loop could be constructed to modulate the TGF-β signaling.…”
Section: Discussionmentioning
confidence: 62%
“…Some of the miRNA that were altered in the circulation e.g. miRs 142-5p, 150-5p and 21-5p have been described in anti-apoptotic responses and may signify cellular compensation for increased hematopoietic death induced by radiation21222324.…”
Section: Discussionmentioning
confidence: 99%
“…84) or IL-22 and IFN 85 , have been proposed to mediate the clearance of rotaviruses by the innate immune system in mice 77 . In addition, rotavirus infection of human Caco-2 cells in vitro 86,87 and in piglets 88 induces transforming growth factor-β (TGFβ) expression, which can downregulate the adaptive immune response to rotavirus infection (see Recurrent infections). In general, rotaviruses have several features that enable them to efficiently evade the innate immune response, leaving the adaptive immune response as a final mechanism for viral clearance.…”
Section: Mechanisms/pathophysiologymentioning
confidence: 99%